A question of detail: matching counterfactuals to actual cause in pre-emption scenarios. (20th July 2021) - Hilton, Denis; Schmeltzer, Christophe; Goulette, Valentin
Abstract: Causal pre-emption scenarios are problematic for the counterfactual framework of causation (CFC) because people judge an action to be the actual cause of an outcome although the outcome would have occurred anyway due to the action of a pre-empted alternative cause. We propose that commonsense causal questions typically probe specific events that actually happened as and how they did, and show that counterfactuals that probe specific events match selections of actual cause, and dissociations only occur with non-specific counterfactuals. In addition, the pre-empted action is often selected as the or an actual cause when it causes the pre-empting action (auto-pre-emption). Judgements of an action's responsibility for the outcome track judgements of actual cause following the legal sine qua non principle. Agent reproach is also influenced by the agent's intention. The effects of causal dependency structure and counterfactual question type are robust across the intentionality of the pre-empting action and scenario content.